Leptin resensitisation: a reversion of leptin-resistant states - Andreoli, Maria Florencia (2019)
Leptin resistance refers to states in which leptin fails to promote its anticipated effects, frequently coexisting with hyperleptinaemia. Leptin resistance is closely associated with obesity and also observed in physiological situations such as pregnancy and in seasonal animals. Leptin resensitisation refers to the reversion of leptin-resistant states and is associated with improvement in endocrine and metabolic disturbances commonly observed in obesity and a sustained decrease of plasma leptin levels, possibly below a critical threshold level. In obesity, leptin resensitisation can be achieved with treatments that reduce body adiposity and leptinaemia, or with some pharmacological compounds, while physiological leptin resistance reverts spontaneously. The restoration of leptin sensitivity could be a useful strategy to treat obesity, maintain weight loss and/or reduce the recidivism rate for weight regain after dieting. This review provides an update and discussion about reversion of leptin-resistant states and modulation of the molecular mechanisms involved in each situation.